1993
DOI: 10.1002/glia.440070106
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow derived elements and resident microglia in brain inflammation

Abstract: Infection of the central nervous (CNS) system by the human immunodeficiency virus (HIV) depends on the migration of infected hematogenous cells into the brain. We thus used quantitative light and electron microscopic immunocytochemistry to study the homing and turnover of bone marrow derived cells in the CNS in radiation bone marrow chimeras under normal conditions and in experimental autoimmune encephalomyelitis (EAE) as an experimental model of brain inflammation. Our studies suggest the following conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
189
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 329 publications
(199 citation statements)
references
References 32 publications
8
189
1
1
Order By: Relevance
“…For many years, microglia were thought to be essentially sessile and to undergo only minor exchanges with peripheral monocyte-macrophage compartments (Hickey and Kimura, 1988;Lassmann et al, 1993). However, the present data indicate that microglia are extensively recruited from bone marrow to brain during the incubation period of scrapie.…”
Section: Discussionmentioning
confidence: 54%
“…For many years, microglia were thought to be essentially sessile and to undergo only minor exchanges with peripheral monocyte-macrophage compartments (Hickey and Kimura, 1988;Lassmann et al, 1993). However, the present data indicate that microglia are extensively recruited from bone marrow to brain during the incubation period of scrapie.…”
Section: Discussionmentioning
confidence: 54%
“…Hickey and Kimura (1988) showed that the perivascular microglia are bone marrow-derived. In contrast, very few parenchymal microglial cells of donor origin were observed despite the fact that non-microglial cells derived from the graft were common within the nervous parenchyma of normal and pathological brains (Hickey and Kimura, 1988;Hickey et al, 1992;Lassmann et al, 1993). These authors suggested that parenchymal microglia were of neuroectodermal origin, or that they derived from bone marrow-derived precursors which enter the nervous system before or about the time of birth.…”
Section: Origin From Primitive Hemopoietic Cellsmentioning
confidence: 99%
“…In contrast, microglia are considered "resting" cells that need to be activated to manifest their full potential. This functional difference may explain why perivascular macrophages are continuously replenished by circulating monocytes, whereas microglia turn over very slowly, if at all, under normal conditions (Matsumoto and Fujiwara, 1987;Hickey and Kimura, 1988;Hickey et al, 1992;Lassmann et al, 1993;Bechmann et al, 2001a,b;Vallières and Sawchenko, 2003). Nevertheless, a significant number of microglia can be replaced by monocytes in response to injury or disease (Popovich and Hickey, 2001;Priller et al, 2001;McMahon et al, 2002;Kokovay and Cunningham, 2005;Ladeby et al, 2005;Schilling et al, 2005;Simard et al, 2006;Remington et al, 2007).…”
Section: Introductionmentioning
confidence: 99%